Don Juan de Austria, un héroe del barroco temprano, en la cultura histórica del siglo xx - Fernando Sánchez-Marcos (Les Dossiers du GRIHL)
This article presents the initial results of an on-going research project: a case-study of twentieth-century European popular historical culture. It focuses on the hero of the Battle of Lepanto, Don Juan of Austria (1547-1578). By using different sources, especially biographies aimed at the general public and historical novels, the changes and continuity in the public image of this figure are analysed; these transformations are defined with respect to the socio-cultural climate, the political context and religious sensitivities. This study of the metamorphosis of an early Baroque hero is preceded by a brief overview of the life and political and military career of this figure, the son of Charles V and Barbara Blomberg.